2004
DOI: 10.1124/jpet.104.074005
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferation-Activated Receptor (PPAR)γ Is Not Necessary for Synthetic PPARγ Agonist Inhibition of Inducible Nitric-Oxide Synthase and Nitric Oxide

Abstract: Peroxisome proliferation-activated receptor (PPAR)␥ agonists inhibit inducible nitric-oxide synthase (iNOS), tumor necrosis factor-␣, and interleukin-6. Because of these effects, synthetic PPAR␥ agonists, including thiazolidinediones, are being studied for their impact on inflammatory disease. The anti-inflammatory concentrations of synthetic PPAR␥ agonists range from 10 to 50 M, whereas their binding affinity for PPAR␥ is in the nanomolar range. The specificity of synthetic PPAR␥ agonists for PPAR␥ at the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 39 publications
1
23
1
1
Order By: Relevance
“…To determine whether the low levels of iNOS and IFN-␥ expression in WT alveolar macrophages were due to the high constitutive expression of PPAR␥, as was shown previously (21), we used GW9662, a known PPAR␥ antagonist (5,23,24). Untreated alveolar macrophages demonstrated no detectable iNOS mRNA expression.…”
Section: Antagonism Of Ppar␥ In Vitro Elevates Inos and Ifn-␥ In Wt Bmentioning
confidence: 93%
See 1 more Smart Citation
“…To determine whether the low levels of iNOS and IFN-␥ expression in WT alveolar macrophages were due to the high constitutive expression of PPAR␥, as was shown previously (21), we used GW9662, a known PPAR␥ antagonist (5,23,24). Untreated alveolar macrophages demonstrated no detectable iNOS mRNA expression.…”
Section: Antagonism Of Ppar␥ In Vitro Elevates Inos and Ifn-␥ In Wt Bmentioning
confidence: 93%
“…IFN-␥ is a known stimulator of iNOS (5,23), and so we thus investigated iNOS mRNA and protein in BAL cells (Fig. 4A).…”
Section: Inos Mrna and Protein Are Elevated In Bal Cellsmentioning
confidence: 99%
“…As mentioned in the introduction, iNOS is essential for the IS-limiting effects of statins (2,49,71) since iNOS is needed for the activation of COX2 (2,6,34,71) and cPLA 2 (65) by S-nitrosylation. Several investigators have suggested that ciglitazone (14), rosiglitazone (15,16), and Pio (15,36) reduce iNOS expression and activity in various experimental models. The present study shows that in contrast to statins, Pio did not augment iNOS expression; moreover, Pio limited IS in iNOS Ϫ/Ϫ mice as it did in the WT mice, whereas statins do not (49,71), emphasizing the fact that the activating pathways of myocardial protection by statins and Pio are different.…”
Section: Role Of Inosmentioning
confidence: 99%
“…20 Moreover, others have reported that thiazolidinediones suppress iNOS expression. [23][24][25] Thus, alteration of COX-2 by S-nitrosylation of a cysteine residue(s) may explain the mechanism by which ATV augments 15-epi-LXA 4 production but probably does not explain how PIO alters COX-2.…”
Section: · Dmentioning
confidence: 99%